2007
DOI: 10.1158/0008-5472.can-06-3439
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Inhibition Activates AMP-Activated Protein Kinase in SKOV3 Human Ovarian Cancer Cells

Abstract: Fatty acid synthase (FAS), the enzyme responsible for the de novo synthesis of fatty acids, is highly expressed in ovarian cancers and most common human carcinomas. Inhibition of FAS and activation of AMP-activated protein kinase (AMPK) have been shown to be cytotoxic to human cancer cells in vitro and in vivo. In this report, we explore the cytotoxic mechanism of action of FAS inhibition and show that C93, a synthetic FAS inhibitor, increases the AMP/ATP ratio, activating AMPK in SKOV3 human ovarian cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
210
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(225 citation statements)
references
References 61 publications
7
210
0
8
Order By: Relevance
“…[20][21][22][23] The cell cycle arrest that follows FASN blockage is associated with increased levels of p21 and p53 in colon, breast, gastrointestinal, and human melanoma tumor cells. 22,[41][42][43] Indeed, ongoing experiments from our laboratory have shown that cerulenin or orlistat significantly increase p21 protein amount in B16-F10 cell lysates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] The cell cycle arrest that follows FASN blockage is associated with increased levels of p21 and p53 in colon, breast, gastrointestinal, and human melanoma tumor cells. 22,[41][42][43] Indeed, ongoing experiments from our laboratory have shown that cerulenin or orlistat significantly increase p21 protein amount in B16-F10 cell lysates.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Conversely, the overexpression of FASN in several human malignancies, such as those of prostate, breast, ovary, melanoma, and soft tissue sarcomas [6][7][8][9][10][11][12][13][14][15][16][17][18][19] has been associated with poor prognosis. FASN inhibition reduces cell proliferation by blocking DNA replication during S-phase, induces apoptosis, [20][21][22][23] and decrease the size of prostate, ovarian, and breast cancer xenografts. 7,8,24 Moreover, the inhibition of FASN activity is chemopreventive in the neu-N mouse model for breast cancer.…”
mentioning
confidence: 99%
“…36,43 Surprisingly, the pharmacological inhibition of FAS in human ovarian cancer cells led to a rapid activation of AMPK within minutes, followed by the induction of substantial cytotoxicity. 44 Blocking AMPK activation with compound C, an AMPK inhibitor, substantially abrogated the cytotoxic effect of FAS inhibition. Thus, it seems that AMPK activation plays a substantial role in the mechanism, whereby FAS inhibition induces cytotoxicity.…”
Section: Selective Ampk Activationmentioning
confidence: 99%
“…Although FAS inhibition can lead to a block in the cell cycle before G 1 , there are data that support an S-phase arrest in breast cancer cells (Zhou et al, 2003) and in colon carcinoma cells ). In the current study, we demonstrated a marked, dose-dependent S-phase block at 24 h after treatment.…”
Section: Hindiii (557)mentioning
confidence: 99%